2015
DOI: 10.1002/jemt.22592
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial biofilm on successful and failed orthodontic mini‐implants—a scanning electron microscopy study

Abstract: Mini-implants have been extensively used in Orthodontics as temporary bone anchorage devices. However, early failure of mini-implants due to mobility might occur and the colonization of their surfaces by pathogenic bacteria has been referred to as one of the contributing factors. In this study, scanning electron microscopy (SEM) was used to assess the presence of microorganisms adhered to the surface of mini-implants that failed due to loss of stability. Twelve self-drilling titanium mini-implants (1.6 mm diam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
4

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
(46 reference statements)
1
6
0
4
Order By: Relevance
“…When a TAD is inserted, a new site is created, which is de ned as the gingival sulcus between the surrounding gingiva and the TAD cervical [24]. In a previous study utilizing SEM, Ferreira discovered bacteria colonization on the head, transmucosal surface, and body segment of TADs [25]. Similarly, in our study, the existence of micro ora was observed on the surface of TADs.…”
Section: Discussionsupporting
confidence: 77%
“…When a TAD is inserted, a new site is created, which is de ned as the gingival sulcus between the surrounding gingiva and the TAD cervical [24]. In a previous study utilizing SEM, Ferreira discovered bacteria colonization on the head, transmucosal surface, and body segment of TADs [25]. Similarly, in our study, the existence of micro ora was observed on the surface of TADs.…”
Section: Discussionsupporting
confidence: 77%
“…There are ethical considerations surrounding the re-use of invasive medical devices in different patients, despite the advantages with respect to costs. TADs may be used again in the same patient if the structural integrity and mechanical properties are not altered following their previous use, and following sterilization [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Los minitornillos son fijaciones de titanio o acero inoxidable que se han utilizado ampliamente en ortodoncia como dispositivos temporales de anclaje óseo (Ferreira et al 2015) permiten un anclaje absoluto o esquelético cuando el tratamiento ortodóntico así lo requiere (Benavides et al 2016) el anclaje esquelético, ha sido la opción de reemplazo al anclaje convencional en situaciones en las que el anclaje se considera crítico, insuficiente o particularmente en los tratamientos poco conservadores que produzca efectos secundarios indeseables (Leo et al 2016).…”
Section: Introductionunclassified